The role of T-box transcription factor TBX3 in rhabdomyosarcoma - Sims, Danica Anne (Department of Human Biology, 2018)
Cancer remains one of the leading causes of death worldwide due to late diagnosis and ineffective treatment options. To address this problem requires the elucidation of the molecular mechanisms, including the signaling pathways and transcription factors that drive cancer initiation and progression. In this regard, our laboratory has been particularly interested in the embryonically important T - box family of transcription factors which has been heavily implicated in promoting initiation and progression of a long list of cancers. For example, the overexpression of the T - box factor TBX3, has been reported to function in promoting immortalization, migration, invasion and tumour formation in a number of epithelial - derived malignancies. Furthermore, our laboratory recently reported that TB X3 is also overexpressed in a wide range of sarcoma subtypes including rhabdomyosarcomas. This suggests that TBX3 may also contribute to the development and/or progression of sarcomas and potentially may serve as a biomarker for their diagnosis and targete d therapy. This is exciting because sarcomas are diverse and heterogeneous cancers with varying clinical behaviours, high rates of metastasis and recurrence and are notoriously resistant to current chemotherapies. However, whether TBX3 is a molecular drive r of these mesenchymal - derived cancers remains to be determined. This project therefore aimed to elucidate the role of TBX3 overexpression in embryonal rhabdomyosarcomas (ERMS) which is the most common soft tissue sarcoma in children and adolescents. To this end, ERMS cell culture models were established in which TBX3 was either stably knocked down or stably overexpressed and the resulting cells were tested for several features of the cancer phenotype using in vitro and in vivo experiments. The results show that TBX3 promotes cell proliferation, anchorage independent growth and cell migration in vitro and tumour formation and invasion in vivo. This study also provides evidence that nucleolin binds to, and co - operates with, TBX3 to promote proliferation and migration of ERMS cells. Furthermore, data from initial experiments reveal that Hsc70 interacts with TBX3, to possibly increase its protein stability, and that oncogenic c - Myc and AKT 1 positively regulat e TBX3 levels in ERMS. This, albeit preliminary data, suggest that Hsc70, c - Myc and AKT1 are responsible, in part, for the overexpression of TBX3 in ERMS. Together findings from this study implicate TBX3 as an oncogene in ERMS and suggest that TBX3, nucleolin, Hsc70, c - Myc and AKT may be used in combination as biomarkers for the diagnosis and targeted therapy of ERMS.